Helicobacter pylori infection selectively increases the risk for carotid atherosclerosis in young males. (December 2019) - Zhang, Linfang; Chen, Zhiheng; Xia, Xiujuan; Chi, Jingshu; Li, Huan; Liu, Xiaoming; Li, Rong; Li, Yixi; Liu, Da; Tian, Delin; Wang, Hui; Petroski, Greg F.; et al.
Abstract: Background and aims: Atherosclerosis is an important contributing factor to cardiovascular mortality. The role of Helicobacter pylori ( H. pylori ) infection in atherosclerosis is inconsistent and sometimes controversial. The present study aimed to determine if H. pylori infection is associated with carotid atherosclerosis. Methods: 17, 613 males and females with both carotid ultrasonic examination and 13 C-urea breath test for H. pylori infection were screened by a major Chinese university hospital from March 2012 to March 2017 for the study. Baseline demographics, cardiac risk factors, and laboratory studies were obtained. After exclusion for pre-specified conditions, 12, 836 individuals were included in the analysis, including 8157 men (63.5%) and 4679 women (36.5%). Analysis was also made for 5-year follow-up data of 1216 subjects (869 males and 347 females) with and without H. pylori infection for development and progression of carotid atherosclerosis. Results: After adjusting for age, sex, body mass index, lipid profile, hypertension, renal function, diabetes mellitus, and smoking, H. pylori infection was found as an independent risk factor for carotid atherosclerosis in males under 50 years, but not in older males or females (odds ratio 1.229, 95% CI 1.054–1.434, p  = 0.009). Follow-up data analysis showed that the incidence of carotid atherosclerosis from no atherosclerosis to detectable lesions was significantly higher in young males with persistent H. pylori infection than those without H. pylori infection ( p  = 0.028) after 3 years. Conclusions: These data suggest that H. pylori infection might be an important risk factor for carotid atherosclerosis in young Chinese males under 50. Graphical abstract: Image 1 Highlights: H. pylori infection might be a novel risk factor for carotid atherosclerosis for young males. The findings might provide an explanation for the observation that males develop atherosclerosis earlier than females. The data could justify screening and treatment for H. pylori infection in young males with premature atherosclerosis.